Pattern of failure and long-term morbidity in patients undergoing postoperative radiotherapy for cervical cancer. Issue 5 (1st September 2006) - Jain, P.; Hunter, R. D.; Livsey, J. E.; Coyle, C.; Kitchener, H. C.; Swindell, R.; Davidson, S. E.
Abstract : The objective of this study was to assess treatment outcomes in a large case series of cervical cancer patients undergoing postoperative radiotherapy in a single center. Case notes of women referred to the Christie Hospital during 1985–1997 for postoperative adjuvant radiotherapy for cervical cancer were reviewed. Of 478 women eligible for analysis, 282 (58.9%) underwent radical hysterectomy and 196 (41.1%) had nonradical hysterectomy. The disease-specific 5-year survival for the study population is 70.1%, with a 5-year risk of developing any recurrence of 30.5% and a 5-year grade 3 morbidity rate of 3.9%. Survival was significantly higher, ie, 80.9% vs 62.7% ( P = 0.0001) and recurrence was significantly lower, ie, 18.6% vs 38.8% ( P < 0.00005) in the group of women who had adjuvant radiotherapy following a nonradical hysterectomy compared with radical surgery. Thirty percent of women having "radical" surgery had positive resection margins and required postoperative adjuvant pelvic radiotherapy. Women with node-positive disease, who received adjuvant radiotherapy, had a high rate of distant metastases. These women would receive chemoradiotherapy now as primary treatment because of the risk of developing distant metastases. If, despite staging investigations, surgery reveals node-positive disease, then these women should receive adjuvant chemoradiotherapy. Survival was better in women who had nonradical surgery due to smaller volume disease when cancers were unsuspected and hence will have been cured by surgery alone. Multidisciplinary team working, as recommended by national guidelines from 1999, should allow better patient selection for treatment.